Daily melatonin administration improves osseointegration in pinealectomized rats - Letícia Pitol PALIN; Tarik Ocon Braga POLO; Fábio Roberto de Souza BATISTA; Pedro Henrique Silva GOMES-FERREIRA; Idelmo Rangel GARCIA JUNIOR; Ana Cláudia ROSSI; Alexandre FREIRE; Leonardo Perez FAVERANI; Doris Hissako SUMIDA; Roberta OKAMOTO (University of São Paulo, 2018)
Abstract The hypothesis of this study was that the peri-implant bone healing of the group of pinealectomized rats would differ from the control group. The samples were subjected to immunohistochemical, microtomographic (total porosity and connectivity density), and fluorochrome (mineralized surface) analyses. Objectives The goal of this study was to investigate the cellular changes and bone remodeling dynamics along the bone/implant interface in pinealectomized rats. Material and Methods The total of 18 adult male rats (Rattus norvegicus albinus, Wistar) was divided into three groups (n=6): control (CO), pinealectomized without melatonin (PNX) and pinealectomized with melatonin (PNXm). All animals were submitted to the first surgery (pinealectomy), except the CO group. Thirty days after the pinealectomy without melatonin, the second surgery was conducted, in which all animals received an implant in each tibia (36 titanium implants with surface treatment were installed - Implalife® São Paulo, SP, Brazil). By gavage, the rats of the PNX group received the vehicle solution, and the procedure. Results Immunohistochemical analysis for runt-related transcription factor 2 (RUNX2), alkaline phosphatase (ALP), osteopontin (OP) and osteocalcin (OC) showed that the bone repair process in the PNXm group was similar to that of the CO group, whereas the PNX group showed a delay. The microtomographic parameters of total porosity [Po(tot)] and bone surface (BS) showed no statistically significant differences, whereas for the connective density (Conn.Dn) a statistical difference was found between the CO and PNXm groups. Fluorochrome analysis of the active mineralized surface showed statistically significant difference between the CO and PNX and between the CO and PNXm groups. Conclusion The absence of the pineal gland impaired the bone repair process during osseointegration, however the daily melatonin replacement was able to restore this response.